2018
DOI: 10.1007/s10554-018-1372-7
|View full text |Cite
|
Sign up to set email alerts
|

One-year optical coherence tomography findings in patients with late and very-late stent thrombosis treated with intravascular imaging guided percutaneous coronary intervention

Abstract: Patients with late/very-late stent thrombosis (ST) are at high risk of recurrent-ST. The mechanisms of recurrent-ST are largely unknown. The objective is to describe the 1-year optical coherence tomography (OCT) findings of patients suffering from late/very-late ST treated with intravascular imaging guided percutaneous coronary intervention (PCI). All consecutive patients with late/very-late ST undergoing intravascular imaging guided PCI were screened to undergo coronary angiography and OCT examination at 1 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Maintaining the patency and integrity of the coronary arteries after successful restoration of coronary blood flow is of paramount importance. In patients undergoing PCI, reocclusion of the coronary artery often occurs within 6 months (Khambata et al, 2011;Ñato et al, 2018;Neumann et al, 2019a,b;Sousa-Uva et al, 2019;Modi et al, 2021). For these patients with reocclusion, their CAD is treated with a bare metal stent or drug-eluting stent (DES), which acts as a platform for new tissue growth (Khambata et al, 2011;Sousa-Uva et al, 2019).…”
Section: Postprocedural Npr-c Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintaining the patency and integrity of the coronary arteries after successful restoration of coronary blood flow is of paramount importance. In patients undergoing PCI, reocclusion of the coronary artery often occurs within 6 months (Khambata et al, 2011;Ñato et al, 2018;Neumann et al, 2019a,b;Sousa-Uva et al, 2019;Modi et al, 2021). For these patients with reocclusion, their CAD is treated with a bare metal stent or drug-eluting stent (DES), which acts as a platform for new tissue growth (Khambata et al, 2011;Sousa-Uva et al, 2019).…”
Section: Postprocedural Npr-c Responsesmentioning
confidence: 99%
“…For these patients with reocclusion, their CAD is treated with a bare metal stent or drug-eluting stent (DES), which acts as a platform for new tissue growth (Khambata et al, 2011;Sousa-Uva et al, 2019). Current DESs (which are now the predominant implanted stents) release antiproliferative drugs that inhibit arterial smooth muscle cell proliferation, which is the most predominant cause of restenosis (Khambata et al, 2011;Ñato et al, 2018;Neumann et al, 2019a,b;Sousa-Uva et al, 2019;Modi et al, 2021). However, these agents may also inhibit endothelial cell proliferation (Matter et al, 2006;Khambata et al, 2011;Ñato et al, 2018;Neumann et al, 2019a,b;Sousa-Uva et al, 2019;Modi et al, 2021), which may increase the thrombogenicity of the stent surface.…”
Section: Postprocedural Npr-c Responsesmentioning
confidence: 99%
“…The patients were divided at baseline according to the most probable causative factor of ST, such as malapposition (17 patients) or other findings (17 patients) and then re-assed at 1 year follow-up. They found that patients that presented with malapposition are more prone to have a worse healing pattern than those who presented with other causes, thus being at higher risk for recurrent ST [17].…”
Section: Evaluation Of Metallic Stentsmentioning
confidence: 99%